Vehicle Emissions and Air Quality: The Early Years (1940s–1950s) - Hoekman, S. Kent; Welstand, J. Steve (Atmosphere, 2021)
During the 1940s, an unusual form of air pollution was experienced in the Los Angeles (LA) area of Southern California. Referred to as LA smog, this pollution differed from previously known air pollution with respect to its temporal patterns (daytime formation and nighttime dissipation), eye irritation, high oxidant levels, and plant damage. Early laboratory and field experimentation discovered the photochemical origins of LA smog. Though mechanistic understanding was incomplete, it was determined that hydrocarbon (HC) compounds in the atmosphere participate in smog formation, enabling build-up of higher ozone concentrations than would otherwise occur. It being a significant source, there was great interest in characterizing and controlling HC emissions from motor vehicles. Considerable work was done in the 1940s and 1950s to understand how emissions varied with vehicle operating conditions and deterioration of engine components. During this time, procedures were developed (and improved) to sample and quantify vehicle emissions. Besides exhaust, HC emissions from crankcase blowby, carburetor evaporation, and fuel tank losses were measured and characterized. Initial versions of both catalytic and non-catalytic exhaust after-treatment systems were developed. The knowledge gained from this pre-1960 work laid the foundation for many advancements that reduced vehicle emissions and improved air quality during subsequent decades.